Olahraga: Sebuah Konsep sebagai Ilmu dan Profesi - Soeningjo Soeningjo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Comprehending sport as a science and also profession needs a clear mapping. Sport can become a concept of science, but can also be regarded as a conceptof a profession. As a science, sport can be contended as a science applying sport asits medium of education. But it also can be stated as an educational science which isin its educational process it uses sport as a means.As a profession, sport is a work which traditionally relates to the extensive, importanteducation: academic education, and also a high standard of behavior. Sport will beregarded as a profession as long as it pays some attention to conditions above.From the scientific standpoint, a sport or a study of sport is still “multidisciplinary”, butlater it becomes “cross-disciplinary”. Meantime, sport education as a discipline impliesa meaning that the sport education owns some natures of a “cross-disciplinary” science.Keyword: Sport, Science, Profession